Creditworthy: Do climate change risks matter for sovereign credit ratings? - Lorenzo Cappiello; Gianluigi Ferrucci; Angela Maddaloni; Veronica Veggente (European Central Bank (ECB), 2025)
Do sovereign credit ratings take into account physical and transition climate risks? This paper empirically addresses this question using a panel dataset that includes a large sample of countries over two decades. The analysis reveals that higher temperature anomalies and more frequent natural disasters-key indicators of physical risk-are associated with lower credit ratings. In contrast, transition risk factors do not appear to be systematically integrated into credit ratings throughout the entire sample period. However, following the Paris Agreement, countries with greater exposure to natural disasters received comparatively lower ratings, suggesting that credit rating agencies are increasingly recognizing the significance of physical risk for sovereign balance sheets. Additionally, more ambitious CO2 emission reduction targets and actual reductions in CO2 emission intensities are associated with higher ratings post-Paris Agreement, indicating that credit rating agencies are beginning to pay more attention to transition risk. At the same time, countries with high levels of debt and those heavily reliant on fossil fuel revenues tend to receive lower ratings after the Paris Agreement. Conversely, sovereigns that stand to gain from the green transition-through revenues from transition-critical materials-are assigned higher sovereign ratings after 2015.
Keywords: G15; G24; F3; F64; H64; 330; Credit ratings; Sovereign bonds; Physical risk; Transition risk; Climate change; bond; credit rating; risk management; financial risk; environmental impact; financial stability